Criminal attempt in the Malaysian computer crimes act 1997 (Act 563) - Nazli, Ismail@Nawang; Aminuddin, Mustaffa; Ammar Abdullah Saeed, Mohammed (2019)
A criminal attempt is an offence in traditional laws as it may cause either damage or the danger of damage. Nonetheless, uncertainty arises with regards to cybercrimes arguably due to the lack of critical attention paid to attempt of committing cybercrime by other researchers in this area. As such, this paper intends to analyse the position of the criminal attempt which is explicitly stipulated in section 7 of the Computer Crimes Act 1997 (CCA). Further, this paper aims to demonstrate related legal issues pertaining to criminal attempt in cybercrimes including mere preparation and its relation to criminal attempts of cybercrimes, mens rea in committing criminal attempt, recklessness in criminal attempt of cybercrimes as well as impossibility defences for cybercrime attempts. In so doing, section 7 of the CCA will be critically scrutinised in solving those issues. Apart from that, the paper will also examine relevant decided cases on criminal attempts for traditional criminal offences. To sum up, merely preparation in cybercrime shall be an attempt, and mens rea is required in a criminal attempt to commit cybercrime but in certain situations knowledge of the risk is enough to be an attempt to commit cybercrime offences.